Two little gardeners - Brown, Margaret Wise, 1910-1952.; Espenscheid, Gertrude E. (Gertrude Elliott); Hurd, Edith Thacher, 1910-1997. (New York : Golden Books, 1979)
Two young gardeners plant vegetable seeds in the spring, watch over the plants as they grow during the summer, and have a bountiful harvest in the fall.
1.9
K-3.
K-3
Keywords: Gardening -- Juvenile fiction; Vegetables -- Juvenile fiction; Gardening -- Fiction; Vegetables -- Fiction; Gardening -- Fiction; Vegetables -- Fiction